Beyond Genera Palmarum: progress and prospects in palm systematics - Baker, William J.; Dransfield, John (Botanical journal of the Linnean Society, 2016)
Abstract The systematic biology of the palm family (Arecaceae) is probably better known than that of any other tropical plant family of comparable size. As a result, the palms are now regarded as a model group for tropical rain forest research. Ten years ago, the first phylogenetic classification of palms was established as a foundation for the second edition of the palm systematic synthesis, Genera Palmarum (GP2), which was published in 2008. Here, we review progress in palm systematics since GP2, summarizing the latest developments in an updated palm classification and schematic phylogenetic tree. To date, the palms comprise 181 genera and c. 2600 species. In just 8 years, six new genera and 200 new species have been described, whereas eight genera have been sunk into synonymy. This reflects the highly dynamic nature of systematic discovery of palms at both forest and phylogenetic frontiers. Palm phylogenetics is a vibrant field, with new trees being generated and utilized in increasingly innovative and ambitious ways. Existing understanding of relationships among the five subfamilies has been confirmed and deep nodes in the subfamilies are crystallizing, especially in subfamilies Arecoideae and Coryphoideae. We conclude that palm systematic knowledge is far from complete and that tools, such as GP2, only stimulate further scientific research and discovery. Despite recent advances, however, many aspects of the palm Tree of Life still remain scarcely known. The vast datasets that the phylogenomic revolution is now bringing to bear on palms promise to elucidate many of these unknowns. The ultimate goal, a species-level phylogenetic tree for palms, is now coming within reach.